2023
DOI: 10.3390/jcdd10060232
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Polymorphisms in ATP-Binding Cassette Transporter Genes on Anthracycline-Induced Early Cardiotoxicity in Patients with Breast Cancer

Abstract: Background. Cardiac side effects associated with anthracycline-based treatment may seriously compromise the prognosis of patients with breast cancer (BC). Evidence shows that genes that operate in drug metabolism can influence the risk of anthracycline-induced cardiotoxicity (AIC). ATP-binding cassette (ABC) transporters could serve as one of the potential biomarkers for AIC risk stratification. We aimed to determine the link between single-nucleotide polymorphisms (SNPs) in several ABC genes (ABCB1 rs1045642,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…36,37,40 Besides these ABCC1 variants, the intronic variant rs4148350 was found to be protective for AIC in both, an exploratory and an independent replication cohort. 32,33 Moreover, this association was corroborated by findings from a more recent study that also found decreased risk of AIC in breast cancer patients carrying the variant T allele, 28 while other studies did not confirm the significant impact of the variant allele. 26,37 In conclusion, there is some evidence for a functional significance and also clinical impact of ABCC2 variants such as the rs246221.However, several other studies failed to find significant effects, or gave contradictory results.…”
Section: Efflux Transporters: Abc Familymentioning
confidence: 61%
See 2 more Smart Citations
“…36,37,40 Besides these ABCC1 variants, the intronic variant rs4148350 was found to be protective for AIC in both, an exploratory and an independent replication cohort. 32,33 Moreover, this association was corroborated by findings from a more recent study that also found decreased risk of AIC in breast cancer patients carrying the variant T allele, 28 while other studies did not confirm the significant impact of the variant allele. 26,37 In conclusion, there is some evidence for a functional significance and also clinical impact of ABCC2 variants such as the rs246221.However, several other studies failed to find significant effects, or gave contradictory results.…”
Section: Efflux Transporters: Abc Familymentioning
confidence: 61%
“…27 Also, in a small study of 71 breast cancer patients, the results of univariate and multivariate logistic regression analyses showed the potential cardioprotective effect of the rs1045642 heterozygous genotype, but it did not reach statistical significance. 28 However, this variant failed to demonstrate any clinical association in non-Hodgkin's lymphoma and diffuse large B-cell lymphoma. 18,29 In the absence of concordance between studies, the findings need to be interpreted with care.…”
Section: Efflux Transporters: Abc Familymentioning
confidence: 88%
See 1 more Smart Citation
“…For example, SNPs (rs1114049) of solute carrier family 28 member 3 have been found to be protective against DIC in hiPSC-CMs [31], and an SNP (rs2229774) in retinoic acid receptor γ (RARG ) is associated with an increased risk of AIC [32]. There is also a link between SNPs and DIC in ATP-binding cassette (ABC) transporters [33]. Transient receptor potential 6 (TRPC6) gene alterations are putative risks for chemotherapy-induced congestive heart failure, and TRPC6 N338S is a gain-of-function mutant that may lead to DIC by increasing Ca 2+ influx within cardiomyocytes [34•].…”
Section: Genomicsmentioning
confidence: 99%